ANALISIS PENGAMBILAN KEPUTUSAN PASANGAN USIA SUBUR UNTUK TIDAK BERPARTISIPASI DALAM PROGRAM KB - Nifueki, Adiyanto Desastra; Riwu, Rut Rosina; Sir, Amelya Betsalonia (Universitas Nusa Cendana, 2022)
ABSTRACT The increasing rate of population growth in the 21st century era has become a separate problem for countries in the world. Indonesia is the fourth most populous country in the world, China, India and the United States. The high rate of population growth that is not accompanied by an increase in the quality of the population, the Indonesian government makes efforts to handle and control population growth by implementing the Family Planning program to improve the welfare of mothers and children and create happy and prosperous small families. The purpose of this study was to determine how the fertile couple's decision not to participate in the family planning program at the Kapan Health Center. This type of research is a qualitative research with an exploratory design. The selection of informants used purposive sampling, collecting ten people, namely PUS mothers who were recorded as not actively using family planning, married, >35 years old and had >3 children. Collecting data by means of in-depth interviews, observation, and documentation. Data were analyzed and presented in the form of narrative text. The results showed that husband/family support influenced the mother's decision not to use family planning, health/family planning officers provided information about family planning through direct counseling and mass media, most of the informants chose not to participate in family planning because of the perceived side effects and the use of natural family planning. The results of the writing can be obtained with the key that EFA's decision not to participate in the family planning program is motivated by the support of the husband/family and the mother feels that it is not suitable for the family planning used and the natural use of family planning. Therefore, it is hoped that the role of the public health center can involve the role of the husband in providing information about the importance of the family planning program for families so as to increase the participation of EFA in the family planning program.